“Influencia de los factores ambientales en la calidad fisicoquímica y microbiológica de la leche bovina en 03 zonas lecheras de la región san martín” - Navarro Ramírez, Enrique (2016)
The present work of investigation h.ad as aim determine the influence of the environmental factors (temperature, precipitation, humidity, solar radiation) in the physicochemical and microbiological quality of the bovine milk of the zones of the Alto Mayo, Bajo Mayo and Huallaga Central of the Region San Martin. For it samples of milk were gathered for four months in every zone of study and were analyzed to obtain his characteristics of density, acidity, fat, protein, salid total, mesófilos aerobic and numeration of coliformes. For the comparison of averages. Duncan test at 5% was used to compare means, in addition Spearman correlation was performed in arder to determine the degree of association between the variables of physicochemical and microbiological quality of milk with environmental factors. Concluded that environmental factors (solar radiation and ambient temperature) affect the density, fat and thus in the amount of total solids in milk, have clase negative.associations (reverse). The relative humidity and precipitation have clase positiva relationships (d irect) in the values of density, fat and total solids in milk cattle. However these meteorological parameters had little or no influence on the acidity and protein content. Besides environmental factors directly affecting the numbering of aerobic mesophilic, especially solar radiation and temperatura, and in the higher temperatura zone (Huallaga Central), high aerobic mesophilic results were obtained in milk; however numbering coliforms were not influenced by environmental factors.